The application of hydrodynamic cavitation to increase the efficiency of the catalytic cracking of vacuum gas oil - S. V. Ivanov; S. I. Vorobyev; V. N. Torhovsky; I. M. Gerzeliev (Тонкие химические технологии, 2013)
The principal possibility of increasing the efficiency of the catalytic cracking of hydrotreated vacuum gas oil by its activation by the action of hydrodynamic cavitation is shown. The achieved effect is to increase the yield of gasoline and to reduce the yield of coke.